Safety and transfer of veterinary drugs from substrate to black soldier fly larvae - K.C.W. van Dongen; E. de Lange; L.L.M. van Asseldonk; L. Zoet; H.J. van der Fels-Klerx (Animal, 2024)
There is an increasing interest in edible insects in Europe for feed and food purposes. Quantitative information on the transfer of chemical hazards from substrates to larvae is needed to evaluate food and feed safety aspects. This evaluation is especially needed when organic substrates or residual streams such as manure will be applied as substrate, contributing to a circular food system. This study investigated the transfer of veterinary drugs from spiked substrate to black soldier fly larvae (Hermetia illucens). Veterinary drugs that are commonly administered to chicken, fattening pigs, and cattle and regularly detected in manure were included: three different antibiotics (enrofloxacin, oxytetracycline, sulfamethoxazole), three coccidiostats (narasin, salinomycin, toltrazuril) and one antiparasitic drug (eprinomectin). The chemicals were spiked to insect substrate to reach final concentrations of 0.5 and 5 mg/kg for the antibiotics and the antiparasitic drug, and 5 and 50 mg/kg for the coccidiostats. Black soldier fly larvae were reared for 1 week on the spiked substrates, and the transfer of the veterinary drugs to the larvae and frass was quantified using liquid chromatography coupled with tandem mass spectrometry. Only oxytetracycline and eprinomectin reduced the average weight and/or survival of the black soldier fly larvae. The transfer of the veterinary drugs to the larvae was on average 19.2% for oxytetracycline, 12% for enrofloxacin, 9.5% for narasin, 8.1% for eprinomectin, 3.9% for salinomycin, 4.2% for toltrazuril, and 0.2% for sulfamethoxazole, relative to concentrations in the substrate. Mass-balance calculations revealed that the larvae seem to metabolise veterinary drugs, and indeed, metabolites of enrofloxacin, sulfamethoxazole, and toltrazuril were detected in the larvae and frass. In conclusion, insect-rearing substrates should be evaluated for the presence of veterinary drug residues to ensure feed (and food) safety, as well as because of possible effects on insect growth.